Transfer pricing in group of companies based on modified Shapley value method. Issue 4 (3rd July 2016) - Ying, Sun; Qiao, Qu; Qiuya, Wang
Abstract: In the Group of companies, a number of members work together to produce some kind of products and share the benefit, which may lead to an issue on the transfer price of intermediate product. The formulation of internal transfer price, in fact, is also a manifestation form of the distribution of income within the group. This article uses cooperative game theory establishing the profit allocation model of group, introduces Shapley value method and modifies the value in consideration of the importance of member companies. Based on the members sharing benefits calculated by the modified Shapley value method, consider the processing cost of each member of the unit itself and determine the internal transfer price of intermediate product. The validity and rationality of this method are proved by the examples.